ANALISIS DINAMIKA PENYERAPAN TENAGA KERJA DI PROVINSI JAWA BARAT - Pratama, Yoga; Al Hamid, Maksum; Sahroini, Halifah; Sugiharti, Rr. Retno (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
Unemployment in West Java Province is relatively high, in other words there are still many workers who have not found work. Based on existing data, the percentage of open unemployment in West Java in 2021 will reach 9.82%. This figure is higher than the percentage of open unemployment in Indonesia, namely 6.26%. The aim of this research is to analyze the influence of the Regency/City Minimum Wage (UMK) on labor absorption, both in a one-way and two-way relationship. This study uses a quantitative approach. The analytical method used is panel data analysis techniques and Granger panel causality models. The research results show that the MSE is directly proportional to the level of labor absorption. The productivity and economic growth variables appear inconsistent in the two models built, meaning that the role of productivity and economic growth in labor absorption is still low. From the causality test, a reciprocal relationship was found between economic growth, productivity and MSEs on labor absorption. This finding is interesting because it allows for another perspective in looking at the dynamics of labor absorption.